Highly efficient elimination of uranium from wastewater with facilely synthesized Mg-Fe layered double hydroxides: Optimum preparation conditions and adsorption kinetics. (1st June 2020) - Li, Peng; Chen, Ping; Liu, Zhipeng; Nie, Shiyong; Wang, Xuegang; Wang, Guanghui; Zhang, Weimin; Chen, Hong; Wang, Lizhang
Highlights: Mg-Fe layered double hydroxides (LDHs) were synthesized to remove uranium in water. Optimal synthetic conditions were comprehensively identified. The adsorbent showed much higher uranium removal capacity than reported LDHs. The adsorption mechanism, kinetics, stability, and selectivity were studied. Good performance was observed in treating actual wastewater from uranium mine. Abstract: Mg-Fe layered double hydroxides (Mg-Fe LDHs) was synthesized via a facile, economical, and environmentally friendly procedure for the elimination of uranium from wastewater. The obtained absorbent was thoroughly investigated by FE-SEM, EDS, TEM, and XRD techniques as well as using bulk uranium adsorption tests, in order to identify optimal synthesis and adsorption conditions. A superior crystalline structure and high uranium adsorption capacity were observed, and the optimal adsorbent is detected as well-crystallized hierarchical amorphous sjogrenite LDHs with particle size appropriately 80 nm, its uranium adsorption capacity was 710.0 mg/g. Uranium was removed in form of UO2 2+ through the complexation reaction with the interlayer anions in the LDHs. The Mg-Fe LDHs showed considerable stability during cyclic uranium adsorption-desorption. Finally, uranium absorption selectivity was demonstrated with authentic uranium mining wastewater treatment. Compared with other reported nanomaterials, this Mg-Fe LDHs would be a promising material for the efficient elimination of uranium from polluted wastewater.